Andrographolide and Fucoidan Induce a Synergistic Antiviral Response in Vitro Against Infectious Pancreatic Necrosis Virus - Imarai-Bahamonde, C; Espinoza-Majmud, D; Reyes-Lopez, F; Vallejos-Vidal, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Andrographolide, fucoidan, or a combination of both compounds were evaluated to determine their effects on the antiviral response in the Atlantic salmon macrophage-like cell line (SHK-1) infected with infectious pancreatic necrosis virus (IPNV). We assessed the transcript expression levels of key molecules involved in the interferon (IFN)-dependent antiviral response, as well as the viral load in cells treated with these compounds. In non-infected cells, incubation with either fucoidan, andrographolide, or a mixture of both resulted in an increase in the transcript expression of IFNα1 and various interferon-stimulated genes (ISGs). In IPNV-infected cells, treatment with either fucoidan or andrographolide separately did not significantly enhance the antiviral response compared to that of infected cells that had not previously been treated with these compounds. In contrast, the combination of andrographolide and fucoidan led to a marked increase in the transcript expression of viperin and a significant reduction in viral load. Overall, combining andrographolide and fucoidan resulted in a greater reduction in IPNV viral load in infected cells than that noted when the compounds were administered individually. Our findings suggest that pre-incubation with this mixture promotes the establishment of a protective antiviral state against IPNV, likely mediated by an IFN-dependent response. © 2025 by the authors.